Explicație pas cu pas:
[tex] \sqrt{5} \times \sqrt{2} = \sqrt{10} [/tex]
[tex] \sqrt{7} \times \sqrt{15} = \sqrt{105} [/tex]
[tex] \sqrt{12} \times \sqrt{18} = 2 \sqrt{3} \times 3 \sqrt{2} = 6 \sqrt{6} [/tex]
[tex]6 \sqrt{6} \times 3 \sqrt{2} = 18 \sqrt{12} = 18 \times 2 \sqrt{3} = 36 \sqrt{3} [/tex]
[tex]2 \sqrt{6} \times 3 = 6 \sqrt{6} [/tex]
[tex]3 \sqrt{18} \times \sqrt{50} = 9 \sqrt{2} \times 5 \sqrt{2} = 90[/tex]
[tex] - 6 \sqrt{3} \times 2 \sqrt{3} = - 12 \sqrt{9} = - 12 \times 3 = - 36[/tex]
[tex]4 \sqrt{2} ( - 2 \sqrt{6} ) = - 8 \sqrt{12} = - 16 \sqrt{3} [/tex]
[tex] - 5 \sqrt{3} \times ( - 3 \sqrt{15} ) = 15 \sqrt{45} = 15 \times 3 \sqrt{5} = 45 \sqrt{5} [/tex]